Improving Motivation and Football Learning Achievement of Junior High School Students by Using Canva-Based Learning Videos (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2024)
This study aimed to analyze the effect of Canva-based learning videos on the motivation and outcomes of soccer passing skill learning of junior high school students. The research method used the mixed method with One Group Pretest-Posttest experimental design and in-depth interviews. The research sample consisted of 34 seventh grade students selected using cluster random sampling. The samples were divided into the experimental group (n=17) that used Canva media and the control group (n=17) that received traditional learning methods. The research instruments utilized learning motivation questionnaires, soccer skills tests, and in-depth interviews to collect qualitative data. The statistical analysis showed a significant increase in the student learning motivation in the experimental group, where the average post-test score increased from 86.7 to 92.8 (p 0.05). Student learning outcomes also significantly improved, with passing skill scores increasing from 10.8 to 4.76 (p 0.05). Qualitative results showed that students who used Canva media felt more motivated because of the interactive and flexible visual presentations during learning activities. However, challenges related to technology access, such as dependence on internet networks, become the limiting factors. In conclusion, Canva-based learning videos could effectively improve the student motivation and outcomes in soccer skill learning. This study contributes to the development of technology-based learning media in Physical Education subject.